Tough geometry problem

Hello can somebody help me find 'D' in terms of 'r' and 'd' please? I've been trying to get the answer for a while now but i end up with a really really complicated expression which i have a feeling isn't really right.. could use some help. Thanks in advance

#Geometry #MathProblem #Math

Note by Jord W
7 years, 8 months ago

No vote yet
16 votes

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

The radius of the LH circle is D+dD+d. Consdering the isosceles triangle with angle θ\theta and base rr, we see that r  =  2(D+d)sin12θ r \; = \; 2(D+d)\sin\tfrac12\theta The other two angles in this isosceles triangle are 9012θ90^\circ-\tfrac12\theta and so, looking at the small right-angled triangle on the right, sin12θ  =  cos(9012θ)  =  dr \sin\tfrac12\theta \; = \; \cos\big(90^\circ-\tfrac12\theta) \; = \; \frac{d}{r} Putting these results together we deduce that r2  =  2(D+d)d r^2 \; = \; 2(D+d)d

Mark Hennings - 7 years, 8 months ago

Log in to reply

found this a different way a short while ago but thanks anyway :)

Jord W - 7 years, 8 months ago

Log in to reply

You should post your solution!

Ahaan Rungta - 7 years, 8 months ago

Log in to reply

@Ahaan Rungta ah its here in one of the other comments :)

Jord W - 7 years, 8 months ago

Nice and easy to understand.

Lokesh Sharma - 7 years, 8 months ago

Hi, This can be done using trigonometry

cos(θ)=DD+dcos(\theta) = \frac{D}{D + d} --------- (1)

Joining the point of intersection of the two circles at the top to the center of the small circle, a beautiful triangle would be formed with,

sin(θ)=rD+dsin(\theta) = \frac{r}{D+d} --------- (2)

Squaring and adding (1) and (2), we get

D2+r2=(D+d)2 D^2 + r^2 = (D + d)^2

Lokesh Sharma - 7 years, 8 months ago

Log in to reply

in case you're wondering how i got what i think is the right answer: cos theta=D/(D+d) as you found however when you make the other identity, if you use the cosine rule for non right angled triangles, you get that r=(D+d)sqrt(2(1-cos theta)), and so you just put the cos theta=D/(D+d) in from earlier and it rearranges pretty quickly to D=r^2/2d -d :)

Jord W - 7 years, 8 months ago

Log in to reply

Thanks for pinning out the problem in my solution and thanks for giving the right solution.

I didn't follow you when you used the cosine rule. Please tell me, which triangle did you used to get it and how did you get r=(D+d)sqrt(2(1-cos theta)).

Lokesh Sharma - 7 years, 8 months ago

Log in to reply

@Lokesh Sharma ah well its the triangle where the three vertices are the centre of the large circle, the centre of the small circle, and one of the intersections of the two circles. if you use this triangle, its got both the large radii subtending the angle theta, and the far side (relative to theta) is the radius of the small circle. Here you can apply the formula c^2=b^2+a^2-2ab cos(C) for which I've found a clearer explanation here: http://drdjw.files.wordpress.com/2012/01/general-triangle.jpg

when you substitute them into that formula for the triangle we're using, you get that r=(D+d)sqrt(2(1-cos theta)), hope that helps :)

Jord W - 7 years, 8 months ago

I think theres a problem with your sintheta = r/(D+d) . when you make that triangle, its an isosceles triangle not a right angled one even though it sort of looks like it should be a right angled one. however thanks anyway, your other identity i think has given me the clue and i think i've found the right answer anyway xD

Jord W - 7 years, 8 months ago

Log in to reply

the radius meets the tangent at the circumference at right angles.

Joseph Varghese - 7 years, 8 months ago

let the radius of the bigger circle be R.

let the perpendicular side of the right angle triangle be x. (having angle θ\theta)

now, join the center of the smaller circle and the point of intersection between the smaller and bigger circle ( we have two point of intersections, but we will take the upper one), so now we have an another right angle triangle so, applying pythogorus theoram in our new right angle triangle :
x2+d2=r2x^{2}+d^{2}=r^{2}

so, x2=r2d2x^{2} = r^{2}-d^{2}___ [1]

now coming back to our bigger right angle triangle

using pythogorus theoram again

we get

x2+D2=R2x^{2}+D^{2}=R^{2}

putting value of x^{2} from eq. 1 and value of R (since R = D+d) we have

r2d2+D2=(D+d)2r^{2}-d^{2}+D^{2} = (D+d)^{2}

r2d2+D2=D2+d2+2Ddr^{2}-d^{2}+D^{2} = D^{2}+d^{2}+2Dd

r22d2=2Ddr^{2}-2d^{2} = 2Dd

D=12r22d2dD= \frac {1}{2} \frac {r^{2}-2d^{2}}{d} ---- answer :)

Rahul Rathee - 7 years, 8 months ago

(r^2)/2 = Dd + d^2

Kshitij Khandelwal - 7 years, 8 months ago

Is the line joining the centre of the bigger circle and the point of intersection of the two circles tangent to the second circle? Can it be proved?

Maharnab Mitra - 7 years, 8 months ago

Firstly we are assuming that the line that we can call RR which is the radius of the larger circle is at a tangent to the perimeter of the smaller circle and a normal to the perimeter of the larger circle (only reason I mention this is because if you zoom on the picture this is perfectly correct) and lets call this point PP. However assuming these, we can draw a triangle from the center of the small circle along the length DD and then a 90°90° angle up to the point PP which we call length xx, hence the hypotenuse of this triangle is RR. We can then make another triangle which starts from the center of the smaller triangle along the length dd and then make another 90°90° angle up to the point PP, the hypotenuse of this triangle is rr. Further more, we know that R=D+dR=D+d, using this information we can model a function of D(r,d)D(r,d):

Using Pythagoras's theorem:

R2=D2+x2R^{2}=D^{2}+x^{2}

r2=d2+x2r^{2}=d^{2}+x^{2}

Hence, when we cancel xx:

R2D2=r2d2R^{2}-D^{2}=r^{2}-d^{2} where R=D+dR=D+d

(D+d)2D2=r2d2(D+d)^{2}-D^{2}=r^{2}-d^{2}

Which simplifies to, r2=2d(D+d)r^{2}=2d(D+d)

Hence, D(r,d)=r22ddD(r,d)=\frac{r^{2}}{2d}-d

Joel Jablonski - 7 years, 8 months ago

wait, is D the radius of the larger circle???

RoneLio Barasi - 7 years, 8 months ago

Log in to reply

no, the radius of the larger circle is D+d

Angel Leon - 7 years, 8 months ago

https://www.facebook.com/groups/572200892829750/ .... link of this solution check it out final relation is r=2 * (D+d) * Cos (theta/2)

Rajendra Singaria - 7 years, 8 months ago

This is solved easily using pythagoras famous equation. c2=a2+b2c^2=a^2 + b^2

the little triangle on the right tells us: r2=d2+h2r^2 = d^2 + h^2

the left side triangle shares the same 'h' side, and we can also say that: (D+d)2=D2+h2(D+d)^2 = D^2 + h^2

Substitute 'h' obtained from the first equation into the second one, and solve fo D in terms of d and r:

(D+d)2=D2+r2d2(D+d)^2 = D^2 + r^2 - d^2

D2+2dD+d2=r2d2+D2D^2 + 2dD + d^2 = r^2 - d^2 + D^2

D=(r2/2d)dD = (r^2/2d) - d

Not so tough, but very fun.

Angel Leon - 7 years, 8 months ago

r/tan@ -d

sai srinivas - 7 years, 7 months ago

use trigonometry. tanθ=rDtan\theta=\frac{r}{D}

tanθ×D=r\tan\theta\times D=r

or,

tan(90θ)×r=D\tan(90-\theta)\times r=D You have more than enough information in this problem.

Fahad Shihab - 7 years, 8 months ago

Log in to reply

Thats in terms of theta as well. my problem is that i can't eliminate theta. btw the 'D' isn't the radius of the circle, but 'D+d' is

Jord W - 7 years, 8 months ago

Fahad S. I don't think tan(theta)=r/d. join the radius of the smaller circle to the point of intersection of both the circles. you would find that the radius becomes the hypotenuse. hence the opposite side of the triangle containing theta is not equal to the radius.

Prithvi S.J. Monteiro - 7 years, 8 months ago

Log in to reply

sorry, I had made one small mistake. It is rD+d\frac{r}{D+d}

Fahad Shihab - 7 years, 8 months ago

D = (r - d sin (teta) ) / (sin (teta) ) ????

RoneLio Barasi - 7 years, 8 months ago
×

Problem Loading...

Note Loading...

Set Loading...